The impact of relational governance on the adaptability of international contractors: a comparative study between China and Korea. Issue 10 (6th July 2020) - Lin, Yi-Hsin; Guo, Yanzhe; Kim, Chan-Joong; Chen, Po-Han; Qian, Mingwei
Abstract : Purpose: In the process of undertaking overseas construction projects, relational governance has become indispensable for project stakeholders. This study examines how relational governance influences contractors' adaptability to foreign situations and whether such associations are positively moderated by international environmental complexity. Design/methodology/approach: A crosssectional survey methodology was applied to collect primary data through questionnaires sent to domestic contractors in China and South Korea (hereafter Korea). Multiple regression analysis was used to test the effects of four dimensions of relational governance on contractor adaptability. Thereafter, the Chinese and Korean subsamples were tested separately through moderated regression analysis to explore differences in the influence of relational governance on adaptability. Findings: The results showed that quality communication, favor exchange and establishing an emotional relationship significantly and positively affected a contractor's adaptability. However, there were significant differences between the Chinese and Korean international contractors in terms of the moderating effects of international environment complexity. Research limitations/implications: East Asian engagement in international development is not limited to China and Korea alone, and the study should be replicated using large representative samples from more countries, such as Japan, to gain a fuller understanding of the influence of relational governance. Originality/value: The results have great significance for the managers of international contractors in East Asian countries and contribute to the research on relational governance and contractor adaptability.